Population health and community health: brokering the two through art and community engagement - Galiatsatos, Panagis; Hailey-Fair, Kimberly; Johnson, Marcie; Vanderpool, Elisabeth A. C.; Stewart, Rosalyn W.; Alexander, Karen; Magsamen, Susan (Frontiers in Public Health, 2024)
The arts and aesthetic experiences have fostered and enhanced relationships between diverse, distinct groups in an effort to build comradery, trust, and engagement. In regards to collaborations between health systems and communities, taking into account strategies to build such relationships is vital in an effort to assure a bidirectional collaboration that implements public health insight and resources effectively. There are many factors warranting consideration when building effective community engagement for health promotion between healthcare systems and local community organizations and residents. Such factors include, but are not limited to, homophily, transitivity, structural holes, and maintaining weak ties. In this brief review, we will explore how the arts can be utilized to broker relationships for healthcare systems implementing community engagement with partnering, diverse social networks. Specifically, we will explore the role of the arts and aesthetic experience to create homophily, foster transitivity and balance, enhance collaboration and build meaningful connections between healthcare systems and social networks to more effectively address health concerns for all involved.